SVAR ANALYSIS OF THE IMPACTS OF CORPORATE TAXATION ON THE MACRO ECONOMY OF LITHUANIA - Klyvienė, V ioleta; Karmelavičius, Jaunius (Ekonomika, 2012)
Abstract. This study aims to investigate the effects of tax policy on the macroeconomic variables of Lithuania. Special attention is devoted to conclusions concerning the impact of corporate taxation. The methodological framework is structural vector autoregression models identified using the Cholesky and Blanchard–Perotti approaches. Investigations of the impact of fiscal policy have been scarce in the empirical literature of Lithuania. The authors of this article use the methodology of assessing the impacts of fiscal policy that has not been used in Lithuania so for.JEL classification: E62, H25, F21.Key words: SVAR model, impulse response functions, fiscal policy, capital tax, investment